2017
DOI: 10.1007/s11250-017-1387-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lameness, claw lesions, and associated risk factors in dairy farms in Selangor, Malaysia

Abstract: The objectives of this cross-sectional study were to estimate the prevalence of lameness, claw lesions, and associated risk factors in dairy farms in Selangor, Malaysia. The sample population was 251 lactating cows from 8 farms assessed for lameness and claw lesions by locomotion scoring and claw assessment respectively while specific animal-based measures were hypothesized as cow-level risk factors. The Wilcoxon rank test and logistic regression were applied to assess the prevalence of lameness, claw lesions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
5
26
1
Order By: Relevance
“…A study conducted in the United Kingdom of seasonally grazed cows showed that the four most common lesions reported by veterinarians were sole ulcer (15.9%), white line disease (15.5%), digital dermatitis (6.7%), and interdigital phlegmon (6.2%) [ 46 ]. The study by Sadiq et al [ 13 ] reported hoof lesions in 87.5% of cows with the highest incidence in cows affected by single lesions (54.2%) and white line disease (61.2%).…”
Section: Prevalence Of Lamenessmentioning
confidence: 99%
See 3 more Smart Citations
“…A study conducted in the United Kingdom of seasonally grazed cows showed that the four most common lesions reported by veterinarians were sole ulcer (15.9%), white line disease (15.5%), digital dermatitis (6.7%), and interdigital phlegmon (6.2%) [ 46 ]. The study by Sadiq et al [ 13 ] reported hoof lesions in 87.5% of cows with the highest incidence in cows affected by single lesions (54.2%) and white line disease (61.2%).…”
Section: Prevalence Of Lamenessmentioning
confidence: 99%
“…Nutrition is a significant factor affecting the healthy growth of the hoof horn [ 4 ]. The composition of the feed ration significantly affects the growth, development, and health of the hooves [ 13 , 26 , 72 , 73 ]. Research has shown that some of the components of the feed ration (minerals, vitamins, amino acids, and fatty acids) play a substantial role in the structural integrity of the hooves [ 1 , 73 ].…”
Section: Factors Influencing the Occurrence Of Lamenessmentioning
confidence: 99%
See 2 more Smart Citations
“…These conditions are multifactorial, as supporting evidence suggest the interplay between rumen acidosis laminitis complex, prepartum metabolic, and hormonal changes affecting the stability of the pedal bone and suspensory apparatus [14,15], as well as biomechanical reaction at the claw-floor interface [16]. In addition, animal-based measures such as body condition loss, reduced thickness of the digital cushion (DC) [17], injured hock, and overgrown claw have been associated with increased odds of CHDLs [18,19].…”
Section: Claw Lesions Causing Lamenessmentioning
confidence: 99%